EXPLORING THE IMPACT OF CONTEXTUAL VOCABULARY TEACHING APPROACHES ON UZBEKISTAN STUDENTS’ ENGLISH LANGUAGE PROFICIENCY: INSIGHTS FROM TASHKENT ENGLISH LANGUAGE TEACHERS’ PERSPECTIVES - Jurayeva Gulbegim (American Journals, 2023)
This study aimed to investigate the effectiveness of contextual approaches to teaching vocabulary in the Uzbekistan education system. A survey was conducted among English language teachers in Tashkent to gather their perspectives on the impact of contextual vocabulary teaching on students’ English language proficiency. The survey results revealed that contextual approaches to teaching vocabulary were perceived as more effective than traditional methods, as they facilitated better retention and application of vocabulary in real-life contexts. Additionally, the study found that incorporating contextual elements into vocabulary teaching increased students’ motivation and engagement, which positively impacted their language learning outcomes. The findings of this study suggest that contextual approaches to teaching vocabulary can be beneficial in enhancing students’ English language proficiency and should be considered as a viable teaching method in the Uzbekistan education system.
Keywords: Contextual approaches, teaching vocabulary, English language teachers, survey, traditional methods, rote memorization, real-life contexts, acquisition, retention, motivation